A dual-emitting inorganic-organic hybrid material with emission intensity enchanced via electron-transfer photochromism. (October 2020) - Liu, Hang; Xie, Zhi-Xin; Lu, Jian; Han, Yong-Fang; Wei, Yong-Qin; Guo, Guo-Cong
Abstract: A new photochromic inorganic-organic hybrid material [( N -MeIQL)BiCl4 ] (1, N -MeIQL +  =  N -methylisoquinolinium) has been solvothermally synthesized. In 1 the N -MeIQL + cation is obtained by in situ alkylation of isoquinoline in the acidized methanol solution, and it is firstly reported that N -MeIQL + acts as an organic template for the design and synthesis of photochromic material. Compound 1 exhibits reversible photochromism between colorless and bright yellow. Moreover, compound 1 displays dual-emitting luminescence and the lifetimes of the two emissions at 410 nm and 640 nm were measured to be 0.71 ns and 0.28 ms, respectively, indicating the fluorescence and phosphorescence characteristics. It is notable that unlike the luminescence quenching of normal photochromic materials in the process of photoinduced coloration, and the emission intensity of 1 can be significantly enhanced via electron-transfer photochromism. The studies of electron-transfer photochromism and photomodulated luminescence provide useful insight into the design of new photoresponsive materials. Graphical abstract: An inorganic-organic hybrid material [( N -MeIQL)BiCl4 ] ( N -MeIQL +  =  N -methylisoquinolinium) exhibits sensitive photochromism between colourless and bright yellow, and displays double emissions with luminescent intensity enchanced in the process of photo-induced coloration. Image 1 Highlights: It explores a new inorganic-organic hybrid electron-transfer photochromic material. N-methylisoquinoline firstly acts as the ligand of photochromic material. It shows dual-emission of phosphorescence and fluorescence at room temperature. It is first reported emission intensity enhanced by electron-transfer photochromism.